2017
DOI: 10.1111/vec.12642
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gastric and bladder tonometry as indicators of tissue perfusion in induced hypotension in dogs

Abstract: Gastric and bladder tonometry can be used to detect hypoperfusion. Further studies are warranted to determine the potential use of gastric and bladder tonometry in assessing dogs in clinical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…This technique measures PbCO 2 via the gas analysis of saline samples collected from the balloon of a Foley catheter inserted into the bladder. The PbCO 2 value is well correlated with DO 2 and PgCO 2 (55,56). However, these results were not confirmed by another group of researchers (57).…”
Section: Bladder Pco 2 (Pbco 2 )mentioning
confidence: 86%
See 1 more Smart Citation
“…This technique measures PbCO 2 via the gas analysis of saline samples collected from the balloon of a Foley catheter inserted into the bladder. The PbCO 2 value is well correlated with DO 2 and PgCO 2 (55,56). However, these results were not confirmed by another group of researchers (57).…”
Section: Bladder Pco 2 (Pbco 2 )mentioning
confidence: 86%
“…The results of several animal studies have suggested that monitoring the intramucosal PCO 2 in the bladder (PbCO 2 ) may be a minimally invasive technique for monitoring perfusion (55)(56)(57). This technique measures PbCO 2 via the gas analysis of saline samples collected from the balloon of a Foley catheter inserted into the bladder.…”
Section: Bladder Pco 2 (Pbco 2 )mentioning
confidence: 99%
“…8 Detection of occult shock is clinically important, and therefore the development of a sensitive and accessible test for this purpose is indicated. 13,16 Measurement of venous plasma lactate concentration, gastric tonometry, and central venous oxygen saturation (ScvO 2 ) is currently used in veterinary and human medicine to detect occult shock, 13,[18][19][20][21] although each has limitations. For example, type B hyperlactatemia may occur without perfusion abnormalities, 22,23 and a high ScvO 2 may be associated with tissue dysoxia.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Gastric tonometry requires placement of a specialized catheter with a balloon into the stomach, and only experimental data are available for dogs. 21 A multimodal approach to the evaluation of perfusion appears beneficial, and it is possible that peripheral perfusion monitoring may develop as a bedside (or cage side) test to complement current methods of perfusion assessment. 4 In people, the core-to-peripheral temperature gradient is typically performed using a rectal or tympanic membrane temperature compared to the temperature of a distal extremity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation